Factors affecting students’ career choices in Morocco - Najia Amini; Youssef Sefri; Mohamed Radid (Institute of Advanced Engineering and Science, 2023)
In a changing socio-economic world, making a career choice has become a complex process that involves many factors. The study is recommended to develop appropriate guiding interventions for career exploration. For this purpose, using a quantitative approach, the study at hand seeks to explain the impact of social context on academic career development. The questionnaire has an internal consistency of about 0.71 and consists of two parts. The first deals with the socio-demographic factor and the second, presented as Likert-type items, contains 17 variables, which are expected to affect students’ career and academic choices. A total of 285 high school students responded to the questionnaire. The study has found that family and teachers’ support, as well as study plans and educational goals, play an important role in students’ career choices. Moreover, using the Mann-Whitney test and the Kruskal-Wallis test, some disparities have been noticed among pupils based on their gender and academic achievement.